Creating value through international strategy - Arino, Africa (Palgrave Macmillan, 2004)
Everyday, more and more companies embark on international business. Through a collection of articles by leading scholars in International Business this book answers fundamental questions such as: How do companies create value through global strategy? What are the sources of value creation? How do companies organize themselves and manage the process of international expansion? How does location specificity matter in this process? Creating Value through Global Strategy will be of interest to academics and professionals in international business and management.